Ag Nanoparticles/AgX (X=Cl, Br and I) Composites with Enhanced Photocatalytic Activity and Low Toxicological Effects. Issue 15 (20th April 2020) - Assis, Marcelo; Groppo Filho, Francisco C.; Pimentel, Dayene S.; Robeldo, Thaiane; Gouveia, Amanda F.; Castro, Tassia F. D.; Fukushima, Hirla C. S.; de Foggi, Camila C.; da Costa, João P. C.; Borra, Ricardo C.; Andrés, Juan; Longo, Elson
Abstract: Periodic structures induced by electron irradiation are a unique phenomenon when electron beams irradiate on the surface of some materials. These periodic structures have potential for technological applications. However, the fuzzy nature of the electron‐induced structuring hinders its further exploration in such applications. In this paper, novel Ag nanoparticle/AgX (X=Cl, Br and I) composites, with enhanced photocatalytic activity and low toxicological effects, were prepared, for the first time, using electron beam irradiation. The remarkable advantage of this approach is that the Ag nanoparticles/AgX composites can be easily prepared in one‐step without the need for high‐pressure conditions, surfactants, ionic liquids, or reducing agents. Furthermore, our method does not involve any toxic substances, which makes the as‐synthesized samples highly applicable for technological applications. The structure, morphology and physicochemical properties of the Ag nanoparticles/AgX composites were studied using various characterization techniques. Using first‐principles calculations based on density functional theory and the quantum theory of atoms in molecules, we reveal how the concentration of excess electrons in the AgX materials induces the formation of the Ag nanoparticles under electron beam irradiation. These results extend the fundamental understanding of the atomic process underlying the mechanism of Ag−X bond rupture observed during the transformation induced via electron irradiation of the AgX crystals by increasing the total number of electrons in the bulk structure. Thus, our findings provide viable guidance for the realization of new materials for the degradation of contaminated wastewater with low toxicity. Abstract : Novel Ag nanoparticle/AgX (X=Cl, Br and I) composites, with enhanced photocatalytic activity and low toxicological effects, were prepared, for the first time, using electron beam irradiation in one‐step without the need for high‐pressure conditions, surfactants, ionic liquids, or reducing agents.